ANALISIS NILAI-NILAI PENDIDIKAN ISLAM DALAM KEGIATAN EKSTRAKULIKULER HIZBUL WATHAN DI SD - Alifiyah, Rifdah; Haryanto, Budi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study aims to analyze the content and implementation of Islamic educational values in the extracurricular activities of Hizbul Wathan at SD Muhammadiyah 9 Ngaban Tanggulangin. This study is motivated by the importance of strengthening character education based on Islamic values through non-formal activities in Muhammadiyah elementary schools. The method used is qualitative research with a phenomenological approach to understand the meaning of the internalization of values that occur in scouting activities. The research subjects included Hizbul Wathan coaches, fourth to sixth grade students, and the school principal. Data collection techniques were carried out through observation, open interviews, and documentation, while data validity was tested through source triangulation. The results showed that the values of faith, worship, morals, and social values were internalized in an integrated manner through habit formation, role modeling, and direct experience. The values of faith and worship are reflected through communal prayer, the habit of greeting others, the correction of intentions, and the interpretation of every activity as a form of obedience to Allah SWT. Moral values are evident in discipline, responsibility, politeness, and the example set by humanistic and compassionate mentors. Meanwhile, social values develop through teamwork, mutual assistance (ta'awun), solidarity, and concern for the school environment. The high level of student participation shows the growth of intrinsic motivation as a result of a religious and enjoyable coaching approach. Thus, Hizbul Wathan functions as an effective medium for the internalization of Islamic educational values in an applicable and contextual manner at the elementary school level. ABSTRAK Penelitian ini bertujuan untuk menganalisis kandungan serta implementasi nilai-nilai pendidikan Islam dalam kegiatan ekstrakurikuler Hizbul Wathan di SD Muhammadiyah 9 Ngaban Tanggulangin. Penelitian ini dilatarbelakangi oleh pentingnya penguatan pendidikan karakter berbasis nilai Islam melalui kegiatan nonformal di sekolah dasar Muhammadiyah. Metode yang digunakan adalah penelitian kualitatif dengan pendekatan fenomenologis untuk memahami makna internalisasi nilai yang terjadi dalam aktivitas kepanduan. Subjek penelitian meliputi pembina Hizbul Wathan, siswa kelas IV–VI, dan kepala sekolah. Teknik pengumpulan data dilakukan melalui observasi, wawancara terbuka, dan dokumentasi, sedangkan keabsahan data diuji melalui triangulasi sumber. Hasil penelitian menunjukkan bahwa nilai aqidah, ibadah, akhlak, dan sosial terinternalisasi secara terpadu melalui pembiasaan, keteladanan, dan pengalaman langsung. Nilai aqidah dan ibadah tercermin melalui doa bersama, pembiasaan salam, pelurusan niat, serta pemaknaan setiap aktivitas sebagai bentuk ketaatan kepada Allah Swt. Nilai akhlak tampak dalam sikap disiplin, tanggung jawab, sopan santun, serta keteladanan pembina yang humanis dan penuh kasih sayang. Sementara itu, nilai sosial berkembang melalui kerja regu, tolong-menolong (ta’awun), solidaritas, dan kepedulian terhadap lingkungan sekolah. Tingginya partisipasi siswa menunjukkan tumbuhnya motivasi intrinsik sebagai hasil pendekatan pembinaan yang religius dan menyenangkan. Dengan demikian, Hizbul Wathan berfungsi sebagai media efektif dalam internalisasi nilai-nilai pendidikan Islam secara aplikatif dan kontekstual di tingkat sekolah dasar.